Analisis Aktivitas Proyek Profil Pelajar Pancasila Dalam Penguatan Karakter Bernalar Kritis Siswa Sekolah Dasar - Nico Ramadhani Alamsyah; Supriyadi Supriyadi (STKIP Singkawang, 2025)
This study aims to describe how the activities in the Pancasila Student Profile Strengthening Project (P5) enhance elementary school students’ critical thinking character. The research was conducted using a descriptive qualitative approach at SD Al Islam Plus Krian, collecting data through interviews, observations, and documentation. The findings reveal that the implementation of P5 such as “Gebyar P5”, thematic discussions, and mind mapping effectively encourages students to think critically, express logical arguments, and reflect on their learning processes. Teachers act as active facilitators who create dialogical and contextual learning environments. Despite challenges like limited time and varying student abilities, the P5 activities proved successful in shaping critically minded, creative students who uphold the values of Pancasila. The study concludes that P5 projects significantly contribute to character formation and the development of students’ critical thinking abilities.